Quantifying the Impact of Research on Matching into Ophthalmology Residency - Bargoud, Albert R.; Thangamathesvaran, Loka; Patel, Varesh R.; Henseler, Robert; Kass, William; Khouri, Albert S. (Journal of Academic Ophthalmology, 2018)
Purpose This article aims to quantify the impact of research on matching into various tiers of ophthalmology residency programs.Design In this study, 340 applicants who matriculated into ophthalmology residency programs in the United States from the class of 2019 were included. Data variables collected for each applicant composed of the following: Hirsch's index (h-index), total number of publications, journal impact factor, type of publication, and number of publications relating to ophthalmology. The primary outcome was tier of ophthalmology program that each applicant matched into, which was determined by two metrics: (1) the h-index of the department's faculty and (2) overall reputation of the residency program as characterized by the U.S. News and World Report Ophthalmology Rankings.Results After multivariate analysis, only the h-index was found to be associated with an increased likelihood of matching at a higher tier program when measuring tier based on the metric of institutional research output (p < 0.0001). However, no research variable was found to be significant on multivariate analysis when assessing the impact of research on matching into a certain tier program based on reputation. The h-index was noted to increase by 1 for every 3.1 papers as the first author, every 4.9 years since the first publication, every 6.4 ophthalmology-related publications, and every publication in a journal with an impact factor of 5.2.Conclusion A higher applicant h-index is associated with matching at an ophthalmology program with greater research output; however, it is not associated with reputation of residency program.
Keywords: ophthalmology residency; medical school; research; bibliometrics; h-index; residency match